The effect of interaction of types and dosages of liquid organic fertilizer on eggplant (Solanum melongena L.) growth and outcome - Junaidi Junaidi; Nugraheni Hadiyanti; Nur Ulfa Turrohmah; Windy Silvyana (Universitas Trunojoyo Madura, 2023)
The use of liquid organic fertilizer (POC) is expected to improve soil physical, chemical and biological fertility. Soil fertility increases, maximum plant growth will increase production both in quality and quantity. This study aims to determine the effect of the interaction between the type of treatment and the dose of POC on the growth and production of eggplant. This study was a factorial experiment consisting of two factors, namely POC types consisting of 2 levels: POC kitchen waste (P1); Banana weevil POC (P2) and POC doses consisting of 4 levels: without POC (D0); 10 ml/tan (D1); 20 ml/tan (D2); 30 ml/tan (D3) with randomization according to a completely randomized design (CRD). Observations were made when the eggplant plants were 10 HST with an interval of 10 days until the plants were 40 days old. The parameters observed were plant height, number of leaves, stem diameter, fruit length per plant, fruit diameter, number of fruit per plant, and fruit weight per plant. Observational data were analyzed using variance, if the results were significantly different it was continued with the smallest significant difference test (LSD) at the 5% level. The results showed that there was no significant interaction between the type of treatment and the dose of POC on all observed parameters. The various POC treatments significantly affected the parameters of plant height and number of leaves at all observed ages, stem diameters at 20 30, 40 DAP, and fruit weight per plant. POC dose treatment significantly affected the parameters of plant height and number of leaves at all ages of observation, stem diameter at 20, 30, and 40 DAP, number of fruit and fruit weight of the plants. Giving banana weevil POC resulted in better eggplant growth and production than kitchen waste POC. POC dose of 30 ml/plant resulted in the best eggplant growth and production. Because the results of the study showed that the effect of POC dose was still linear (the higher the POC dose, the higher the production).